A VERSION APPLICATION FOR A CHILD OPPOSITE THE LAW - Azmiati Zuliah; Dian Hardian Silalahi; Adi Putra; Rilawadi Sahputra (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2022)
AbstractAll children are entitled to live, to grow, to thrive and to be protected from violence and discrimination. In reality, though, the number of children with legal problems increases significantly over the years. The treatment of children in trouble with the law suggests that they are often treated as "miniatures" of criminal adults. The study aims to assess the capacity of law enforcement officials, including police, prosecutors, judges, government, and related agencies. Recognizing the needs of these institutions, we implemented an alternating diversion of restorative justice approach. The government has projected the rupiah's exchange rate at rp9,100 per dollar in the Jakarta interbank spot market on Monday as investors bought the local unit on Wednesday. The study USES a descriptive qualitative study method with a prescriptive quality of research with an empirical approach and USES primary and secondary data. The data gathered is analyzed by organizing the data into categories, detailing them in units, and drawing conclusions that are easily understood. The results of this study have concluded that understanding with law enforcement officers especially at the police level is better because the completion of children's cases outside the law can be resolved at the investigative level. Most of the whistleblower (90,48%) Understanding about complainers of judges, prosecutors, police and lawyers, including ngos, social work units and bapas staff.Keyword: diversion, restorative justice, son